DuCLOX-2/5 Inhibition Attenuates Inflammatory Response and Induces Mitochondrial Apoptosis for Mammary Gland Chemoprevention - Gautam, Swetlana; Rawat, Atul K.; Sammi, Shreesh R.; Roy, Subhadeep; Singh, Manjari; Devi, Uma; Yadav, Rajnish K.; Singh, Lakhveer; Rawat, Jitendra K.; Ansari, Mohd N.; Saeedan, Abdulaziz S.; Kumar, Dinesh; et al. (Frontiers in Pharmacology, 2018)
The present study is a pursuit to define implications of dual cyclooxygenase-2 (COX-2) and 5-lipoxygenase (5-LOX) (DuCLOX-2/5) inhibition on various aspects of cancer augmentation and chemoprevention. The monotherapy and combination therapy of zaltoprofen (COX-2 inhibitor) and zileuton (5-LOX inhibitor) were validated for their effect against methyl nitrosourea (MNU) induced mammary gland carcinoma in albino wistar rats. The combination therapy demarcated significant effect upon the cellular proliferation as evidenced through decreased in alveolar bud count and restoration of the histopathological architecture when compared to toxic control. DuCLOX-2/5 inhibition also upregulated levels of caspase 3 and caspase 8, and restored oxidative stress markers (GSH, TBARs, protein carbonyl, SOD and catalase). The immunoblotting and qRT-PCR studies revealed the participation of mitochondrial mediated death apoptosis pathway along with favourable regulation of COX-2, 5-LOX and NF-κB. Aforementioned combination restored the metabolic changes to normal when scrutinized through 1H NMR studies. Henceforth, the DuCLOX-2/5 inhibition was recorded to import significant anticancer effects in comparison to either of the individual treatments.